(untitled) (The Review of Diabetic Studies, 2024)
Introduction: Effective infection control in healthcare requires coordination among dental practitioners, laboratory specialists, preventive medicine professionals, and anaesthesia technicians. Integration of these roles enhances collaboration, reduces infection risks, and improves workflow efficiency in complex clinical settings. Aim of Work: This study examines the impact of integrated infection control practices on patient safety, clinical outcomes, and workflow efficiency, while addressing ethical concerns, accountability, and communication challenges across healthcare disciplines. Methods: A mixed-method approach was used, combining questionnaires, interviews, focus groups, observations, and simulations. Participants included dental, laboratory, preventive medicine, and anaesthesia professionals. Data focused on the effectiveness of interprofessional collaboration, protocol adherence, and workflow coordination. Findings: Interdisciplinary collaboration improved adherence to infection control protocols, reduced infections, and enhanced patient safety and clinical outcomes. Key ethical concerns included role clarity, informed consent, confidentiality, and equitable resource allocation. Conclusion: Coordinated infection control among dental, laboratory, preventive medicine, and anaesthesia professionals enhances patient safety, workflow efficiency, and clinical outcomes. Structured collaboration, continuous training, and clear responsibilities are essential for sustainable and effective practices.